Civil Servants and Democratic Backsliding: The Role of Managerial Signals - Mads Pieter van Luttervelt; Mathias Rask Østergaard-Nielsen; Martin Bækgaard; Zuzana Murdoch; Benny Geys (Journal of Public Administration Research and Theory, 2026)
Abstract Political efforts to weaken democratic institutions place civil servants in a dilemma between political responsiveness and protecting democratic values. As civil servants are embedded in the political-administrative hierarchy, we argue that signals from their direct hierarchical superiors are critical to understand how civil servants address this dilemma. Using a randomized survey experiment among Norwegian national-level civil servants (N = 1,446) and ordered logistic regression models, we find that democratic backsliding increases opposition to government wishes, internal and external voice, and consideration of exit from the organization. Managerial signals moderate these effects: civil servants are more inclined to voice concerns or consider exit when managers signal responsiveness to government wishes. In a conceptual replication and extension among US federal, state and local civil servants (N = 504) using ordered logistic regression models, we likewise find a greater inclination to exit if the manager signals responsiveness to government wishes, but also that respondents are less inclined to voice concerns to the manager. Overall, our findings imply that managerial signals within the political-administrative hierarchy are shaping civil servants’ immediate reactions to democratic backsliding.